THE INFLUENCE OF IMPLEMENTING CORPORATE GOVERNANCE PRINCIPLES TOWARDS CORPORATE FINANCIAL PERFORMANCE IN BANKING SECTOR - Karina Krissanti; Apriani Dorkas Rambu Atahau (Journal of Economics, Business, and Accountancy Ventura, 2010)
History has recorded that banking scandals have never ceased to happen. It implies that the urgency for banking sector to manage banks prudently by implementing good governance practice. The good government practice is designed to improve bank performance, protect stakeholder interest, and increase adherence to prescribed regulations, legislations and also generally accepted ethical values. The implementation of good corporate governance in long period of time has an impact on bank performance because good corporate governance principles are the foundation of banking organizing process. This research aims to test the impact of corporate governance principle implementation on financial performance of banking sector. The secondary data were obtained from Indonesian Capital Market Directory (ICMD) and Annual Report from the Faculty Data Centre. The result shows that the implementation of corporate governance has positive impact on financial performance of banking sector as measured by Return on Equity (ROE). This suggests that in the future, the banking sector should proceed to implement corporate governance principle especially on disclosing some aspects such as environment, quality, and standardization.